The Matter of Size: A Review of the Research on Relationships Between School and District Size, Pupil Achievement and Cost - Austin D. Swanson (Journal of Research in Rural Education, 1988)
This article reviews the research on relationships between school and district size, pupil achievement and cost. The evidence is evaluated in terms of the educational reform movement and the growing sophistication of telecommunications. Policy implications for school district consolidation and the role of intermediate districts are discussed.